Kir2.1 Channel Contributes to Hypokalemia-Induced Abnormal Pacemaker Activities of Cardiomyocytes With Inward Rectification - Jinhua Lv; Yangxin Jiang; Jin Zeng; Dongchuan Zuo (Frontiers in Bioscience-Landmark)
Background: Hypokalemia induces abnormal spontaneous pacemaker activities of cardiomyocytes, which is strongly associated with fatal cardiac arrhythmias caused by hypokalemia. However, the mechanism remains unclear. Methods: For the study of the mechanisms associated with hypokalemia, optical mapping recordings were performed on isolated murine hearts perfused with hypokalemia solutions, which allows for the concurrent examination of membrane potential and calcium transient morphology and arrhythmogenesis. Human Kir2.1, Kir2.1-E224G mutant, or Kir4.1 channels were constructed with lentiviral vectors. Patch clamp recordings were performed to verify the corresponding currents of these constructed channels in the heterologous expression system chinese hamster ovary (CHO) cells, and to explore how Kir2.1 channels influence the resting membrane potentials of human iPSC-derived cardiomyocytes (hiPSC-CMs) when exposed to low [K+]e. Results: Isolated murine hearts perfused with hypokalemia solution (1 mmol/L) developed a high frequency of spontaneous ventricular tachycardia (VT), which was initiated as an after-depolarization triggered activity associated with Ca2+ overload. The VT was maintained by abnormal spontaneous pacemaker activities caused by membrane potential depolarization. In response to 1 mmol/L [K+]e, hiPSC-CMs overexpressing Kir2.1 channels exhibited membrane potential depolarization, leading to the induction of abnormal pacemaker activities. The cells overexpressing rectification-deficient Kir2.1-E224G mutant channels or weak rectification Kir4.1 channels exhibited membrane potential hyperpolarization without the occurrence of abnormal pacemaker activities. Conclusions: Kir2.1 channel-mediated membrane potential depolarization contributes to hypokalemia-induced abnormal spontaneous pacemaker activities of cardiomyocytes. The inward rectification of Kir2.1 channels plays a critical role in this process.